Presence of antioxidative agent, Pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro- in newly isolated Streptomyces mangrovisoli sp. nov. - Ser, Hooi-Leng; Palanisamy, Uma D.; Yin, Wai-Fong; Abd Malek, Sri N.; Chan, Kok-Gan; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2015)
A novel Streptomyces, strain MUSC 149T was isolated from mangrove soil. A polyphasic approach was used to study the taxonomy of MUSC 149T, which shows a range of phylogenetic and chemotaxonomic properties consistent with those of the members of the genus Streptomyces. The diamino acid of the cell wall peptidoglycan was LL-diaminopimelic acid. The predominant menaquinones were identified as MK9(H8) and MK9(H6). Phylogenetic analysis indicated that closely related strains include Streptomyces rhizophilus NBRC 108885T (99.2 % sequence similarity), Streptomyces gramineus NBRC 107863T (98.7 %) and Streptomyces graminisoli NBRC 108883T (98.5 %). The DNA–DNA relatedness values between MUSC 149T and closely related type strains ranged from 12.4 ± 3.3 % to 27.3 ± 1.9 %. The DNA G + C content was determined to be 72.7 mol%. The extract of MUSC 149T exhibited strong antioxidant activity and chemical analysis reported identification of an antioxidant agent, Pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-. These data showed that metabolites of MUSC 149T shall be useful as preventive agent against free-radical associated diseases. Based on the polyphasic study of MUSC 149T, the strain merits assignment to a novel species, for which the name Streptomyces mangrovisoli sp. nov. is proposed. The type strain is MUSC 149T (= MCCC 1K00699T = DSM 100438T).